Evaluation of the Potential Protective Role of Galangin Associated with Gold Nanoparticles in the Histological and Functional Structure of Testes of Adult Male Albino Mice Administrated with Carbon Tetrachloride - Bassem Sultan Abeed; Hanady Salim Al-Shmgani (مجلة بغداد للعلوم)
Galangin (Gal) is a natural flavonoid sourced from the roots of the plant Albina Kalanga. It possesses a variety of pharmacological activities, such as antioxidant, anticancer, and anti-inflammatory. The current study aims to enhance the efficacy of galangin through the use of gold nanoparticles as a drug delivery system against CCl4-induced toxicity in the testicular tissue of male albino mice. Forty-two albino mice were divided into seven groups (6 mice/group), treatment with carbon tetrachloride solution for two weeks by intraperitoneal injection, (1 ml/kg) once a week for all groups except the control group, after which a group was injected with gold nanoparticles and two groups were injected with galangin in two concentrations, and two groups were injected with AuNPs + Gal conjugation solution with two concentrations. The animals' bodies were weighed and blood samples were obtained for testosterone hormone analysis and testicles for the purpose of weighing and histological study at the end of the experiments. The study showed that the testicular tissue of mice treated with CCl4 had a different pathology compared to the control group, the testosterone hormone levels in the CCl4 group were significantly higher than those of the control group. Results from the AuNPs+Gal group showed a significant reduction in the effects of CCl4 toxicity on mice testicles, with testosterone levels are returning to normal and histological testicle structures improving, the ratio of testicle weights to animal body weight in the group injected with AuNPs was significantly higher than that of the control and CCl4 groups. In conclusion, the results revealed that galangin combined with gold nanoparticles could effectively reduced the histological and functional tissue damages caused by CCl4, presenting a promising natural solution that needs to be further developed